The Effect Of Workload And Motivation On Organizational Commitment Towards Non Goverment Official - Nadila, Indah Aenun; Swasti, Ika Korika; Rosyanti, Daisy Marthina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The role of non-civil servant (non-ASN) employees has become increasingly vital in line with improvements and growing complexity in public services. However, non-ASN employees in Indonesia often face various challenges, such as uncertain employment status and high workloads. These issues can pragmatically influence employees' loyalty and attachment to the organization, particularly for non-ASN employees within the Department of Industry and Manpower in Surabaya. This study aims to examine the influence of workload and motivation on organizational commitment among non-ASN employees, using a quantitative approach. Data were collected through an online questionnaire distributed to 60 respondents and analyzed using Partial Least Squares (PLS) to derive relevant findings. The results indicate that workload has no significant effect on organizational commitment, suggesting that the amount or intensity of work assigned to employees does not directly determine their loyalty and attachment to the organization. However, motivation was found to significantly affect organizational commitment, meaning that the higher the employees' motivation, the stronger their commitment to the organization. Future research is recommended to explore mediating variables such as leadership style and organizational culture